Alkaline water electrolysis membrane and preparation process thereof, and alkaline water electrolysis device

By designing a porous carrier and a porous hydrophilic layer in an alkaline electrolytic hydrophilic separator, the problem of high ohmic resistance of the separator is solved by using the combination of polymer polymer and inorganic hydrophilic particles, and lower resistance and better electrolytic performance are achieved.

CN119753752APending Publication Date: 2025-04-04HANGZHOU COBETTER FILTRATION EQUIPMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411992088.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the existing alkaline electrolytic process, the ohmic resistance of the separator is high, resulting in a low current density, which increases the number of electrolytic cells/electrolytic stacks and production costs.

Method used

By adding a porous support and a porous hydrophilic layer to the alkaline electrolytic separator, the structure formed by polymer polymers and inorganic hydrophilic particles is used to improve the hydrophilicity and pore accessibility of the separator, thereby reducing resistance.

Benefits of technology

Lower resistance and better electrolytic performance are achieved, while avoiding the increase in resistance and gas crossover problems caused by excessive addition of inorganic hydrophilic particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753752A_ABST
    Figure CN119753752A_ABST
Patent Text Reader

Abstract

The present invention relates to an alkaline electrolysis water diaphragm and a preparation process thereof, an alkaline electrolysis water device, the alkaline electrolysis water diaphragm comprising a porous carrier and a porous hydrophilic layer arranged on both sides of the porous carrier, the porous hydrophilic layer comprising a high molecular polymer and an inorganic hydrophilic particle, the porous hydrophilic layer at least partially penetrates into the pore structure of the porous carrier, wherein the alkaline electrolysis water diaphragm satisfies the following conditions simultaneously: (1) the water contact angles on both sides of the alkaline electrolysis water diaphragm surface are both greater than or equal to 60°; (2) the pore accessibility of the alkaline electrolysis water diaphragm is 90%-99%, and the pore accessibility is the ratio of the alkali absorption rate of the alkaline electrolysis water diaphragm at 60°C and 30wt% KOH solution soaked for 4 hours to the alkali absorption rate at 90°C and 30wt% KOH solution soaked for 4 hours. The alkaline electrolysis water diaphragm that simultaneously satisfies the water contact angle and pore accessibility range of the present invention has a lower resistance, and thus has a more excellent electrolytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen production by water electrolysis, and in particular to an alkaline water electrolysis diaphragm and a preparation process thereof, and an alkaline water electrolysis device. Background Art

[0002] Hydrogen production by water electrolysis is a way to achieve energy conversion and storage, and can be widely used in electricity conversion and storage such as solar power generation, wind power generation, and hydropower generation.

[0003] At present, the main methods of hydrogen production by water electrolysis include proton exchange membrane (PEM) water electrolysis, polymer anion exchange membrane (AEM) water electrolysis and alkaline water electrolysis. Among them, the PEM water electrolysis hydrogen production process has a higher current density and a shorter start-up time, but requires precious metals such as platinum or iridium as catalysts for bipolar plates, which greatly limits the reduction of the cost of water electrolysis hydrogen production; although the AEM water electrolysis hydrogen production process shows good electrolysis performance, the stability of AEM in an alkaline environment is poor, and it is easy to react with hydroxide ions, resulting in degradation and failure of the anion exchange group. Compared with the PEM water electrolysis hydrogen production process and the AEM water electrolysis hydrogen production process, the alkaline water electrolysis hydrogen production process has good compatibility with non-precious metal catalysts, high maturity, high chemical stability, and more importantly, its cost is lower and more attractive. However, the current density of the alkaline water electrolysis process for hydrogen production is relatively low, which is often due to the high ohmic resistance of the diaphragm and the low kinetics caused by the use of non-precious metal catalysts. This low current density makes the number of electrolyzers / electrolyzers required for the alkaline water electrolysis process significantly higher at the same hydrogen production capacity, which also leads to an increase in cost.

[0004] Therefore, one of the current research hotspots is how to reduce the ohmic resistance of the diaphragm in the alkaline water electrolysis process to improve the working efficiency of the electrolytic cell and obtain lower production costs.

[0005] For example, the Chinese invention patent with publication number CN115125582A discloses a method for preparing an organic-inorganic composite membrane in an alkaline electrolysis device, which introduces inorganic particles and layered double metal hydroxide (LDH) as fillers, wherein the inorganic particles can improve the hydrophilicity of the diaphragm, promote the conduction of the electrolyte in the positive and negative electrodes, and reduce the resistance of the diaphragm, and the addition of LDH further improves the hydrophilicity of the diaphragm, and it has good intrinsic OH - Conductivity to further reduce the membrane resistance. The Chinese invention patent with publication number CN116334690A discloses a highly hydrophilic alkaline water electrolysis membrane, whose hydrophilicity can be adjusted by changing the amount of sulfonated polysulfone added, and as the amount of addition increases, the better the hydrophilicity of the membrane, the lower the corresponding membrane resistance.

[0006] It can be seen that the better the hydrophilicity of the diaphragm, the lower its resistance tends to be. Therefore, improving the hydrophilicity of the diaphragm is a common pursuit at present. Summary of the invention

[0007] For diaphragms with a high molecular polymer with poor hydrophilicity as the substrate, the hydrophilicity of the diaphragm can be improved by adding inorganic hydrophilic particles. Therefore, as the amount of inorganic hydrophilic particles added increases, the hydrophilicity of the diaphragm increases accordingly, and the pore structure in the diaphragm is naturally easier to be wetted by alkaline solution (or electrolyte) to form an ion path, thereby obtaining lower resistance.

[0008] However, the applicant found that as the amount of inorganic hydrophilic particles added continued to increase, the hydrophilicity continued to increase, but the resistance did not continue to decrease. After reaching a low value, it showed an upward trend. It can be seen that hydrophilicity and resistance are not positively correlated, which is different from the current conventional wisdom.

[0009] In this regard, the applicant has found that the factors affecting the resistance of the diaphragm are different at different stages of addition of inorganic hydrophilic particles. At the beginning, the diaphragm is mainly composed of polymers with poor hydrophilicity and is difficult to be wetted by alkali solution. At this time, even the addition of a small amount of inorganic hydrophilic particles can significantly improve the hydrophilicity of the diaphragm, thereby greatly increasing the possibility of forming ion transfer channels in the diaphragm. Therefore, the influence of hydrophilicity on resistance is the main factor; however, with the increase in the amount of inorganic hydrophilic particles added, not only does the improvement effect of inorganic hydrophilic particles on the hydrophilicity of the diaphragm have a marginal decreasing effect, but the resistance reduction brought about by hydrophilicity also shows a marginal decreasing effect. The increase in the amount of inorganic hydrophilic particles added has a negative impact on the number of pore flow channels that can form ion transfer channels in the diaphragm. The negative impact is continuously accumulated, so in the later stage, the negative impact brought about by the decrease in the number of effective flow channels becomes the main factor affecting the resistance, resulting in an increase in hydrophilicity but an increase in resistance.

[0010] Based on this, the first aspect of the present invention provides an alkaline water electrolysis membrane, which includes a porous carrier and a porous hydrophilic layer arranged on both sides of the porous carrier, the porous hydrophilic layer includes a polymer and inorganic hydrophilic particles, and the porous hydrophilic layer at least partially penetrates into the pore structure of the porous carrier, wherein the polymer includes but is not limited to at least one of polysulfone, polyethersulfone and polyphenylsulfone, and the inorganic hydrophilic particles include but are not limited to at least one of zirconium oxide, titanium oxide, bismuth oxide, cerium oxide, magnesium oxide, zirconium hydroxide, titanium hydroxide, bismuth hydroxide, cerium hydroxide, magnesium hydroxide and barium sulfate.

[0011] Specifically, the alkaline water electrolysis membrane satisfies the following conditions at the same time:

[0012] (1) The water contact angles on both sides of the alkaline water electrolysis membrane are greater than or equal to 60°;

[0013] (2) The pore accessibility of the alkaline water electrolysis membrane is 90%-99%, wherein the pore accessibility is the ratio of the alkali absorption rate of the alkaline water electrolysis membrane when immersed in a 30wt% KOH solution at 60°C for 4 hours to the alkali absorption rate of the alkaline water electrolysis membrane when immersed in a 30wt% KOH solution at 90°C for 4 hours.

[0014] In the present invention, pore accessibility is the ratio of the alkali absorption rate of the diaphragm at 60°C and 90°C. At 60°C, the viscosity of the alkali solution is relatively large, while at 90°C, as the temperature of the alkali solution increases, its viscosity and surface tension will decrease, and its permeability will increase, so it is easier to penetrate into the small pore structure in the diaphragm that is difficult to wet and fill at 60°C.

[0015] Therefore, the pore accessibility can characterize the ease with which the pore structure of the diaphragm is wetted and filled with alkali solution. If the pore structure of the diaphragm can be completely filled with alkali solution at 60°C, the alkali absorption rate of the diaphragm at 60°C and 90°C should be the same, and the pore accessibility is 100%. In this case, it means that there is basically no small pore structure that is difficult to wet in the diaphragm, and the hydrophilicity is good at this time, indicating that a large number of large-particle inorganic particles are added (the inorganic particles are too small, and the pore size formed between the inorganic particles is small and difficult to wet; there are too few inorganic particles, the hydrophilicity is insufficient, and some pore structures are also difficult to wet). Only in this way can a large number of large pore structures that are easy to penetrate and wet be introduced. On the one hand, these large-sized pore flow channel structures have weak gas cross-protection capabilities (such as the mixing of hydrogen and oxygen at the anode and cathode, which may cause serious production safety accidents and is therefore unacceptable). On the other hand, the hydrogen bond network density of this structure is slightly low (the dispersed inorganic particles can produce a hydrogen bond network with good intrinsic OH - Conductivity), which will also lead to increased resistance; on the contrary, if the pore structure of the diaphragm is difficult to fill at 60℃ but easier to fill at 90℃, the alkali absorption rate of the diaphragm at 60℃ and 90℃ should be quite different, and the pore accessibility cannot reach 100%. In this case, either the hydrophilicity is too poor to make some pore structures unable to be wetted, or there are a large number of pores that are too small to be wetted at low temperatures and can only be wetted at high temperatures. This means that there are too many small pore structures and the pore size is too small. At this time, the hydrophilicity may be high, but the number of ion transfer channels is relatively small, so the resistance is increased.

[0016] In short, if the amount of inorganic hydrophilic particles added is too low, regardless of the particle size of the inorganic hydrophilic particles, the hydrophilicity of the diaphragm is low, and the low pore accessibility of the diaphragm is predictable; and with excessive addition of inorganic hydrophilic particles, if the particle size of the inorganic hydrophilic particles is too small, a large number of small pore structures that are difficult to wet at low temperatures will be introduced, resulting in a decrease in pore accessibility, and if the particle size of the inorganic hydrophilic particles is too large, a large number of large pore flow channel structures that increase the possibility of gas crossing will be introduced. Therefore, it is difficult to solve the problem that the present invention needs to solve by controlling the particle size of the inorganic hydrophilic particles alone or by controlling the amount of inorganic hydrophilic particles added alone, and pore accessibility is actually a comprehensive control of the amount of inorganic hydrophilic particles added and the particle size of the inorganic hydrophilic particles on hydrophilicity, pore flow channel size, etc.

[0017] Combined with the previous analysis, the present invention first limits the water contact angle of the diaphragm to be greater than or equal to 60°, that is, the present application does not want the diaphragm to have too good hydrophilicity, which actually limits the upper limit of the amount of inorganic hydrophilic particles added; secondly, the pore accessibility is limited to 90%-99%, so that the lower limit of the amount of inorganic hydrophilic particles added is determined by the lower limit of the pore accessibility being not less than 90%, which also determines that the particle size of the inorganic hydrophilic particles should not be too low, avoiding the problem of the pore structure being difficult to be wetted due to the low amount of inorganic hydrophilic particles added or the small particle size of the inorganic hydrophilic particles. The upper limit of the pore accessibility is not greater than 99%, which determines that the pore size formed by the inorganic hydrophilic particles cannot be too large, that is, the particle size of the inorganic hydrophilic particles should not be too large, so that the diaphragm has good hydrophilicity and there are a large number of large-size pore structures that are easy to wet, leading to gas cross-over problems. The combined effect of water contact angle and pore accessibility indicates that the diaphragm has a reasonable amount of inorganic hydrophilic particles added and the particle size of the inorganic hydrophilic particles is reasonable, so that the hydrogen bond network formed in the diaphragm is denser, which in turn makes the diaphragm have lower resistance and further has better electrolytic performance. However, the resistance will not increase due to excessive addition of inorganic hydrophilic particles, nor will the introduction of a large number of large pore structures lead to gas cross-over problems.

[0018] In fact, in the process of producing hydrogen by electrolysis of water, the energy used is often unstable (such as photovoltaic power supply, wind power, etc.), and the gas produced by electrolysis also fluctuates, which is more likely to produce uneven impact; and due to the circulation of the electrolyte, the inevitable vibration of the equipment operation, etc., the diaphragm will be in a vibrating and pressure-unbalanced working condition for a long time. Whether from the perspective of the mechanical strength of the diaphragm or from the perspective of the local air permeability of the diaphragm, the diaphragm in the present invention can reduce stress concentration, avoid local damage, and is more conducive to achieving good anti-gas cross performance during long-term use.

[0019] It can be understood that the water contact angle uses the membrane as a sample, captures the optical image of deionized water droplets falling on the membrane surface through a water contact angle tester, and measures the tangent angle between its gas-liquid interface and liquid-solid interface to obtain the water contact angle data.

[0020] The alkali absorption rate data Q at different temperatures is calculated by the following formula: Q = (M1-M0) / M0, wherein M1 is the mass of the alkaline water electrolysis membrane per unit area in the saturated wet state after being immersed in a 30wt% KOH solution for 4 hours at the test temperature, and its unit is g; M0 is the mass of the alkaline water electrolysis membrane per unit area in the dry state, and its unit is g.

[0021] It should be noted that, although the diaphragm in the present application is mainly used for hydrogen production by alkaline water electrolysis, it can also be used for electrolysis of hydrogen and chlorine in the chlor-alkali industry.

[0022] Preferably, the pore accessibility of the alkaline water electrolysis membrane is 92%-98%, and the water contact angles on both side surfaces of the alkaline water electrolysis membrane are both less than or equal to 80°.

[0023] Through the above technical scheme, the pore accessibility range and water contact angle data are further optimized, which means, on the one hand, that the diaphragm has a better lower limit of hydrophilicity, ensuring good wetting properties between the diaphragm and the alkali solution; on the other hand, the number of undersized pore channels formed by the inorganic hydrophilic particles is further reduced, thereby making the diaphragm have lower resistance; in addition, the upper limit of the diaphragm pore accessibility is no more than 98%, which means that the diaphragm has better anti-gas crossover capability.

[0024] Furthermore, the alkali absorption rate Q of the alkaline water electrolysis membrane is 70%-90%, and the alkali absorption rate Q is calculated by the following formula: Q=(M1-M0) / M0, wherein M1 is the mass of the alkaline water electrolysis membrane per unit area in a saturated wet state immersed in a 30wt% KOH solution for 4 hours at 90°C, and its unit is g; M0 is the mass of the alkaline water electrolysis membrane per unit area in a dry state, and its unit is g.

[0025] Through the above technical scheme, the alkali absorption rate of the diaphragm at 90°C is controlled at 70%-90%, which means that the pore channel structure in the diaphragm is easily wetted by the alkali solution, and the diaphragm has a higher pore channel volume. Due to the upper limit of the pore accessibility of the diaphragm, although the diaphragm has a higher pore channel volume, the size of the pore channel is not too large or too small. Therefore, the diaphragm of the present application has further preferred pore channel size and number of pore channels, so as to obtain preferred low resistance and ensure excellent anti-gas crossover capability.

[0026] The diaphragm includes macropores formed by polymers and small pores formed between inorganic hydrophilic particles after being filled with inorganic hydrophilic particles, and the macroporous structure formed by the surface polymer is also an important factor affecting wettability. Therefore, the SEM average pore size of the surface pores of the alkaline water electrolysis membrane is preferably 200nm-1200nm, and / or, the surface pores of the alkaline water electrolysis membrane have a pore area percentage of 20%-60% on the surface of the alkaline water electrolysis membrane.

[0027] Through the above technical scheme, the pores on the surface of the diaphragm are a macroporous structure formed by a polymer, and the SEM average pore size of the surface pores is controlled to be not less than 200nm and the pore area percentage is not less than 20%, which can avoid the pore size of the surface pores being too small, and the alkali solution being blocked by a large area of ​​polymer with poor hydrophilicity and unable to enter the diaphragm well; and the pore size of the surface pores is not greater than 1200nm and the pore area percentage is not greater than 60%, which can reduce the possibility of inorganic hydrophilic particles falling off from the diaphragm due to impact, vibration, etc. during use.

[0028] Further optimizing the surface pore area ratio of the alkaline water electrolysis membrane (the total pore area ratio per unit area of ​​the membrane surface) is beneficial to the alkaline water electrolysis membrane to balance high air tightness and low resistance. If the pore area ratio is too low, it means that a large area of ​​the membrane surface is a high molecular polymer with poor hydrophilicity, which can easily lead to bubble adsorption and wettability problems of the membrane; if the pore area ratio is too high, on the one hand, the impact resistance of the membrane surface is weak, and on the other hand, it is difficult to avoid bubbles from invading the inside of the membrane. It is understandable that the surface pores of the alkaline water electrolysis membrane include but are not limited to any point value of 20%, 30%, 40%, 50%, 60% or any range value between the two.

[0029] In the present application, whether it is the surface pore size of the diaphragm or the microscopic morphological parameters such as the surface pore area percentage of the diaphragm, they are all the average data of the surfaces on both sides of the diaphragm, and the surface magnified image of the diaphragm can be obtained by an electron microscope, an ultra-depth of field microscope and other equipment, and the corresponding data can be obtained by manual measurement (such as CAD, nano measure and other software) or automatic measurement (such as image J and other software).

[0030] Furthermore, when the SEM average pore size of the surface pores of the diaphragm is larger than the SEM median pore size, the pore size data presents a positively skewed distribution, and the pore size is distributed on the small pore side. When the SEM average pore size of the surface pores of the diaphragm is smaller than the SEM median pore size, the pore size data presents a negatively skewed distribution, and the pore size is distributed on the large pore side. In the present invention, the SEM average pore size of the surface pores of the diaphragm is preferably larger than the SEM median pore size, so that the proportion of small pores is higher. Furthermore, the ratio of the SEM median pore size of the surface pores of the diaphragm to the SEM average pore size is preferably 0.7-1.2, and more preferably 0.9-1.1, so that the diaphragm has a lower resistance.

[0031] Through the above technical solution, the pore accessibility can characterize the pore channel distribution of the entire diaphragm, but it cannot reflect the actual pore distribution on the surface of the diaphragm. For the diaphragm, the surfaces on both sides are directly in contact with bubbles, face impact, and contact with electrolytes. Therefore, the actual pore structure distribution on both sides of the surface has a great influence on the performance of the diaphragm.

[0032] Specifically, on the basis that the diaphragm as a whole has a large number of pore flow channel structures that can be wetted but are not too large in size, the diaphragm surface pores in the present application have a non-excessive skewed distribution, which indicates that the pores on the diaphragm surface are neither excessively small nor excessively large. When the average value of the surface pore diameter is greater than its median value (i.e., the ratio of the two is less than 1), the pore size data is positively skewed, and the pore size is mainly distributed on the small pore side, and when the average value is less than the median value (the ratio of the two is greater than 1), the pore size data is negatively skewed, and the pore size is distributed on the large pore side. The ratio of the two is controlled to be 0.7-1.2, indicating that the pore structure on the diaphragm surface is more inclined to normal distribution rather than skewed distribution, and for the surface of the diaphragm, although a large number of small pore structures can indeed further avoid gas adsorption on the surface and bubble invasion into the inside of the diaphragm, it also hinders the electrolyte from entering the inside of the diaphragm, making it difficult to ensure sufficient and rapid wetting of the diaphragm, resulting in excessive electrolysis start-up voltage; on the contrary, although the electrolyte is more likely to enter the inside of the diaphragm for sufficient and rapid wetting, the possibility of gas surface adsorption and bubble invasion also increases accordingly.

[0033] In short, the ratio of the SEM median pore size to the SEM average pore size of the surface pores of the alkaline water electrolysis membrane reflects the surface pore distribution of the alkaline water electrolysis membrane. Under certain proportions, the surface pores of the alkaline water electrolysis membrane have more small pores and appropriate large pores, which is conducive to further balancing the airtightness and resistance properties of the membrane. It is understood that the ratio of the SEM median pore size to the SEM average pore size of the surface pores of the alkaline water electrolysis membrane includes but is not limited to any point value of 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or any range value between the two. If the SEM average pore size of the surface pores of the alkaline water electrolysis membrane is larger than the SEM median pore size, it means that the pore size data is positively skewed, that is, the pore size distribution is mainly small pores; if the SEM average pore size of the surface pores of the alkaline water electrolysis membrane is smaller than the SEM median pore size, it means that the pore size data is negatively skewed, that is, the pore size distribution is mainly large pores, which may make it difficult to achieve a balance between the airtightness and resistance performance of the membrane.

[0034] Optionally, on the surface of the alkaline water electrolysis membrane, the average value of the minimum distance between adjacent pore structures is 100nm-500nm, more preferably 150nm-350nm, so that the pore distribution can be more uniform and the membrane has lower resistance.

[0035] Through the above technical solution, since the inorganic hydrophilic particles are mainly distributed in the pore structure, controlling the minimum distance between adjacent pore structures is actually controlling the mutual distance between the hydrophilic sites on the surface of the diaphragm. The minimum distance between adjacent pore structures is no more than 500nm, so a denser hydrophilic node network can be formed on the surface of the diaphragm, making it difficult for bubbles to be adsorbed on the surface of the diaphragm. The minimum distance between adjacent pore structures is no less than 100nm, which can reduce the possibility of gas intrusion into a large number of pore structures.

[0036] In short, the spatial distribution of the pore structure is further regulated, the high pore density structure of the alkaline water electrolysis membrane is optimized, and the principle that the high molecular polymer area distributed between the pores is small and it is not easy to adsorb bubbles is utilized, thereby further reducing the resistance of the alkaline water electrolysis membrane. It is understood that on the surface of the alkaline water electrolysis membrane, the average value of the minimum distance between adjacent pore structures includes but is not limited to any point value of 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm or any range value between the two, preferably 150nm-350nm.

[0037] Optionally, the IPA initial bubble point of the alkaline water electrolysis membrane is not less than 0.8 bar. The membrane of the present application has a larger IPA bubble point, and the IPA bubble point often corresponds to the largest hole flow channel structure in the membrane, so that the maximum pore size of the membrane can be guaranteed not to be too large, avoiding gas crossing, and the PMI minimum pore size of the alkaline water electrolysis membrane is not less than 10nm, so that the minimum pore size of the membrane can be guaranteed not to be too small, and there is no completely unwettable pore structure. Furthermore, the membrane can have a lower resistance and a better ability to prevent gas crossing.

[0038] Furthermore, the PMI average pore size of the alkaline water electrolysis membrane is preferably 15 nm-50 nm, and the porosity of the alkaline water electrolysis membrane is preferably 50%-70%.

[0039] In this application, the IPA bubble point is measured by a bubble point tester using a diaphragm as a sample, wherein the test liquid is IPA (isopropyl alcohol) and the test gas is nitrogen or air. The porosity is measured by using a diaphragm as a sample, measuring the mass of the diaphragm under dry and water-wet conditions, respectively, obtaining the water absorption mass of the diaphragm to obtain the pore volume of the diaphragm, and calculating the porosity by the ratio of the pore volume to the diaphragm volume. Of course, other conventional test methods in the field are also acceptable.

[0040] The thickness of the alkaline electrolysis water diaphragm of the present invention is preferably 150μm-600μm. When the thickness of the diaphragm is larger, under the same pore size, it is more difficult for the alkali solution to completely penetrate and wet at low temperatures, and the gas crossover is also more difficult. At this time, an appropriate amount of macroporous structure can be formed in the diaphragm by using inorganic hydrophilic particles with larger particle size to ensure the number of effective flow channels and ensure low resistance. Correspondingly, when the thickness of the diaphragm is small, inorganic hydrophilic particles with smaller particle size can be introduced to ensure that the gas does not cross, a dense hydrogen bond network and a relatively short flow channel ensure low resistance. Therefore, the ratio of the SEM average particle size of the inorganic hydrophilic particles described in the diaphragm of the present invention to the thickness of the alkaline electrolysis water diaphragm is preferably 5nm / 100μm-150nm / 100μm.

[0041] The smaller the air permeability of the diaphragm, the higher the porosity, the lower the tortuosity, and the smaller the corresponding resistance. However, too high a porosity will reduce the mechanical properties and anti-opening performance of the diaphragm. Therefore, preferably, under a pressure difference of 5 bar, the air permeability of the alkaline water electrolysis diaphragm is 2L / min / cm 2 -6.5L / min / cm 2 .

[0042] Optionally, after being placed in water at 100° C. for 15 minutes, the dimensional change rate of the alkaline water electrolysis membrane is no more than 3%, so that the membrane has high stability and is more reliable when used. It can be understood that the so-called dimensional change rate refers to its area change rate.

[0043] Optionally, in a 30 wt% KOH solution at 90°C, the ionic resistance per unit thickness of the alkaline water electrolysis membrane is not greater than 35 mΩ·cm 2 / 100μm, so the diaphragm has excellent conductive properties and can reduce the consumption of electrical energy.

[0044] In a second aspect, the present invention further provides a process for preparing the alkaline water electrolysis membrane, comprising the following process steps:

[0045] S1. Preparation of casting solution. First, the inorganic hydrophilic particles are mixed with the solvent system and stirred to disperse. Then, a polymer is added to fully dissolve to obtain a casting solution. In the casting solution, the total mass of the polymer and the inorganic hydrophilic particles accounts for 15wt%-25wt%, and the mass ratio of the polymer and the inorganic hydrophilic particles is 1:2-1:8. The inorganic hydrophilic particles include fine particles with an average particle size of 30nm-350nm and coarse particles with an average particle size of 70nm-500nm. The average particle size of the fine particles is smaller than that of the coarse particles. The ratio of the fine particles to the coarse particles is 5:1-10:1. The solvent system includes a first good solvent and a first poor solvent, and the mass ratio of the first good solvent is 80wt%-90wt%.

[0046] S2, casting, casting the casting liquid onto the porous carrier to form a coating film;

[0047] S3, pre-gelling, placing the coated film in an environment with a humidity of 70% RH-90% RH and a temperature of 50°C-70°C for pre-treatment for 5s-20s to obtain a gel film;

[0048] S4, phase separation solidification, placing the gel film in a phase separation bath to completely phase separate and solidify the casting liquid to obtain a solidified film, wherein the phase separation bath comprises a second good solvent and a second poor solvent, and the mass proportion of the second good solvent is 5%-15%, and the temperature of the phase separation bath is 10°C-15°C lower than the temperature of the casting liquid;

[0049] S5, post-treatment, washing and drying the solidified film to obtain an alkaline water electrolysis membrane.

[0050] Through the above technical scheme, the greater the amount of inorganic hydrophilic particles added, the lower the water contact angle of the diaphragm, the smaller the particle size of the inorganic hydrophilic particles, the larger the specific surface area, the lower the water contact angle of the diaphragm, and the pore accessibility is mainly affected by the comprehensive influence of pore size and hydrophilicity, the more small pore structures, the worse the hydrophilicity, the worse the low-temperature wettability, and the lower the pore accessibility. Therefore, in step S1 of the present invention, inorganic hydrophilic particles of different sizes are blended, and the proportion of the two is controlled, and a small amount of inorganic hydrophilic particles with large particle size are used to be mixed with a large number of inorganic hydrophilic particles with small particle size, so as to avoid excessive dense stacking of inorganic particles with small particle size to form a large number of small-sized pore flow channel structures that are difficult to be wetted, thereby forming an actual disconnection, and small particles provide a dense hydrogen bond network to ensure hydrophilicity, so that a diaphragm with a water contact angle and pore accessibility that meets the requirements can be obtained.

[0051] The average particle size of the inorganic hydrophilic particles in this application is

[0052] In addition, the casting liquid in the present application specifically adopts a solvent system obtained by compounding a good solvent and a poor solvent, and controls the proportion of the good solvent in the solvent system to be 80-90wt%, which can ensure that the high molecular polymer is completely dissolved on the one hand, and on the other hand, a small amount of poor solvent introduced can make the casting liquid in a slightly unstable state, reducing the difficulty of phase separation of the casting liquid. In conjunction with the high humidity environmental treatment in the subsequent pre-gel treatment, a small amount of non-solvent can further enter the casting liquid, and in conjunction with the small amount of non-solvent already present in the casting liquid, the unstable state of the casting liquid is further improved, making it easier to cause pre-gel nucleation, and promoting the phase separation process of the casting liquid in the subsequent phase separation bath.

[0053] In addition, the present invention disperses the inorganic hydrophilic particles first, which can avoid the difficulty in uniform dispersion due to high viscosity after the high molecular polymer is added.

[0054] In step S2, the thickness of the coating film can be controlled by dipping with a scraper, dipping with a roller spacing, or by two extrusion heads controlling the polymer thickness on both sides and attaching them to the support. The present invention does not limit this.

[0055] In step S3, by pre-treatment under a certain humidity, the non-solvent water can be allowed to penetrate into the membrane to a certain extent to generate nucleation points, and at the same time, with the temperature limit, the viscosity can be reduced to promote water penetration. Specifically, in an environment with a high humidity of 70% RH-90% RH and a high temperature of 50-70°C, the viscosity of the casting liquid is low, the water in the environment is absorbed by the casting liquid and quickly penetrates, and the solvent system in the casting liquid will inevitably evaporate a small amount at a higher temperature. Therefore, in the pre-gel treatment step, the solvent system in the casting liquid actually produces a change in which the proportion of good solvents decreases and the proportion of bad solvents increases, and this change reduces the stability of the casting liquid and makes it easier to produce phase separation nuclei. And although the environmental humidity is high, the water content is still limited. Therefore, the pre-gel treatment time is a long 5-20s, which ensures that more water is absorbed by the casting liquid and a certain solvent system evaporates, and on the other hand, ensures that the absorbed water penetrates evenly in the diaphragm.

[0056] During the phase separation and solidification process of step S4, the phase separation bath is basically a non-solvent, so the phase separation is very fast after the material exchange. It is generally believed that the higher the temperature, the lower the viscosity, the smaller the permeation resistance, the faster the material exchange between the membrane and the phase separation bath, and naturally the faster the phase separation, and the easier it is to produce a small pore structure.

[0057] However, the inventors of the present application unexpectedly discovered that for the system of the present application, within a certain temperature range, in the phase separation solidification stage, appropriately lowering the temperature can obtain the desired pore structure. This may be due to the fact that, as the temperature increases, the viscosity of the casting solution is indeed getting lower and lower, but its changing trend is becoming more and more moderate. In other words, within a certain and relatively high temperature range, although the viscosity changes, the variation is not large. Correspondingly, for the special composite solvent system casting solution of the present application and the system whose stability has decreased after the pre-gel treatment, within this temperature range, as the temperature decreases, the solubility or instability of the polymer decreases, and the phase separation core formed in conjunction with the pre-gel step can also promote the phase separation. Therefore, although the temperature in the phase separation and solidification stage is lower than that of the casting liquid (the casting liquid is heated to 50-70°C in the pre-gel step), it is not suitable to be lower than 15°C to ensure that the casting liquid still has a low viscosity for rapid material exchange. The temperature difference of at least 10°C ensures that the solubility of the high molecular polymer in the casting liquid, which is a composite solvent system, is not too high, and the stability is reduced. The combination of the two can ensure that the system can quickly separate into phases, thereby obtaining a special microscopic pore structure with small pore size and high porosity.

[0058] Inorganic hydrophilic particles are prone to hydrogen bonding and agglomeration, so a water-soluble inorganic salt is also added to the casting solution of the present invention, and the amount of the water-soluble inorganic salt added is 0.05-0.1 times the mass of the inorganic hydrophilic particles added. The water-soluble inorganic salt is at least one of calcium chloride, magnesium chloride and sodium chloride, and when preparing the casting solution, the water-soluble inorganic salt and the inorganic hydrophilic particles are added together into a solvent system for blending and dispersion. The anions and cations generated by the addition of the water-soluble inorganic salt have a strong charge effect and change the ion concentration of the system, thereby changing the charge distribution around the inorganic hydrophilic particles, and further improving the problem of agglomeration caused by hydrogen bonding between the inorganic hydrophilic particles.

[0059] Optionally, the first good solvent and the second good solvent are each independently selected from at least one of butyl lactate, dimethyl sulfoxide, dimethylformamide, caprolactam, methyl acetate, ethyl acetate, N-ethylpyrrolidone, dimethylacetamide and N-methylpyrrolidone, and the first poor solvent and the second poor solvent are both water.

[0060] The third aspect of the present invention further provides an alkaline water electrolysis device, which includes the alkaline water electrolysis membrane, thereby improving the working efficiency of the alkaline water electrolysis device and reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a schematic diagram of a scanning electron microscope (SEM) of one side surface of the alkaline water electrolysis diaphragm obtained in Example 1, with a magnification of 10K times;

[0062] Figure 2 This is a schematic diagram of a scanning electron microscope (SEM) of the other side surface of the alkaline water electrolysis diaphragm obtained in Example 1, with a magnification of 10K times;

[0063] Figure 3 This is a schematic diagram of a scanning electron microscope (SEM) of a cross section of the alkaline water electrolysis diaphragm obtained in Example 1, with a magnification of 20K times;

[0064] Figure 4 is a schematic diagram of a scanning electron microscope (SEM) of zirconium dioxide with an average particle size of 30 nm used in Example 2, and the magnification is 100K times;

[0065] Figure 5 This is a schematic diagram of a scanning electron microscope (SEM) of a cross section of the alkaline water electrolysis diaphragm obtained in Comparative Example 1, with a magnification of 10K times;

[0066] Figure 6 This is a schematic diagram of a scanning electron microscope (SEM) of a cross section of the alkaline water electrolysis membrane obtained in Comparative Example 2, with a magnification of 10K times. DETAILED DESCRIPTION

[0067] Example 1

[0068] S1. Preparation of casting solution: firstly, inorganic hydrophilic particles, water-soluble inorganic salt and solvent system are mixed and stirred and dispersed according to the mass ratio, so that the inorganic hydrophilic particles are evenly dispersed in the solvent system, and then the polymer is added and stirred continuously until the polymer is fully dissolved to obtain casting solution. Specifically, based on 100 parts by weight of the casting solution, the casting solution includes the following components in parts by weight:

[0069] 4 parts of high molecular polymer, wherein the high molecular polymer is M w = 110,000 polyethersulfone;

[0070] There are 16 parts of inorganic hydrophilic particles in total, that is, the mass ratio of the high molecular polymer to the inorganic hydrophilic particles is 1:4; the inorganic hydrophilic particles are a blend of fine particles and coarse particles in a mass ratio of 7:1, that is, the inorganic hydrophilic particles are specifically a blend of 14 parts of fine particles and 2 parts of coarse particles, the fine particles are zirconium dioxide with an average particle size of 200nm, and the coarse particles are zirconium dioxide with an average particle size of 300nm.

[0071] 1.3 parts of water-soluble inorganic salt, that is, the water-soluble inorganic salt is about 0.08 times the amount of inorganic hydrophilic particles added. In this embodiment, the water-soluble inorganic salt is sodium chloride.

[0072] The solvent system has a total of 78.7 parts, and the solvent system specifically includes a first good solvent with a mass proportion of 85wt% and a first poor solvent with a mass proportion of 15wt%. In this embodiment, the first good solvent is N-ethylpyrrolidone, and the first poor solvent is water.

[0073] S2, casting, casting the casting liquid onto the porous carrier to form a coating film; in this embodiment, a PPS woven mesh with a thickness of about 100 μm and 160 mesh is used as the porous carrier, and the porous carrier is immersed in the casting liquid, and the thickness of the casting liquid on both sides is controlled by rolling on both sides and controlling the distance between the rollers.

[0074] S3, pre-gelling, placing the coated film in an environment with a humidity of 80% RH and a temperature of 60° C. for pre-treatment for 13 seconds to obtain a gel film.

[0075] S4, phase separation solidification, placing the gel film in a phase separation bath to make the casting liquid completely phase-solidified to obtain a solidified film, and the temperature of the phase separation bath is 12°C lower than the temperature of the casting liquid. Since the casting liquid is heated to 60°C in step S3, the temperature of the phase separation bath is 48°C. In this embodiment, the phase separation bath includes a third good solvent with a mass proportion of 10wt% and a third poor solvent with a mass proportion of 90wt%, and the third good solvent is N-ethylpyrrolidone, and the second poor solvent is water.

[0076] S5, post-treatment, washing the cured film 3-5 times and drying to obtain a separator. The rest is detailed in the table below.

[0077] Example 2

[0078] The main difference between Example 2 and Example 1 is that the formula of the casting liquid and various process parameters are adjusted. Specifically, this embodiment increases the overall solid content of the casting liquid, especially the proportion of high molecular polymers, so that the casting liquid has a higher proportion of film-forming substances; and adjusts the particle size of fine particles and the particle size of coarse particles in the inorganic hydrophilic particles and adjusts the mass ratio of the two, so that the inorganic particles are more inclined to form small-sized pore channels; further adjusts the lower temperature and lower humidity of the environment during the pre-gel treatment, and the treatment time, so that the volatilization of the solvent in the casting liquid and the absorption of water in the environment are less in the pre-gel stage. Therefore, the overall change of the casting liquid system is small, the pre-gel nucleation process is relatively slow, and the lower good solvent content of the phase bath in the phase separation solidification stage is combined, so that the casting liquid tends to quickly separate into small pores in the phase separation solidification stage. See the table below for details.

[0079] Example 3

[0080] The main difference between Example 3 and Example 1 is that the formula of the casting liquid and various process parameters are adjusted. Specifically, this embodiment reduces the overall solid content of the casting liquid, especially the proportion of high molecular weight polymers, so that the casting liquid has a lower proportion of film-forming substances; and adjusts the particle size of fine particles and coarse particles in the inorganic hydrophilic particles and adjusts the mass ratio of the two, so that the inorganic particles are more inclined to form large-sized pores and flow channels; further adjusts the higher temperature and higher humidity of the environment during the pre-gel treatment, and the treatment time, so that the solvent in the casting liquid volatilizes and absorbs more water in the environment during the pre-gel stage. Therefore, the overall change of the casting liquid system is large, and the pre-gel nucleation process is relatively fast. Even in the pre-gel stage, further phase separation has occurred and the polymer-rich phase and the solvent-rich phase have each merged and expanded in size. The higher good solvent content of the phase bath in the phase separation solidification stage makes the casting liquid tend to slowly separate into phases to form a macroporous structure during the phase separation solidification stage. See the table below for details.

[0081] Embodiment 4-5

[0082] The main difference between Example 4 and Example 1 is that the casting liquid formula and various process parameters are adjusted. Specifically, due to the higher solid content, lower proportion of solvent system and lower proportion of good solvent in the solvent system in this embodiment, the casting liquid has relatively weak stability. In conjunction with the adjustment of the higher temperature and higher humidity of the environment during the pre-gel treatment, the volatilization of the solvent in the casting liquid and the absorption of water in the environment during the pre-gel stage are relatively high. Therefore, the overall change of the casting liquid system is relatively large, and the stability of the casting liquid is further reduced. This reduces the uniformity of the phase separation in the phase separation and solidification stage, and reduces the uniformity of the pore structure on the surface of the diaphragm. See the table below for details.

[0083] Example 5 mainly reduces the solid content of the casting liquid and increases the proportion of the solvent system and the proportion of a higher good solvent in the solvent system, making the casting liquid more stable. Further adjusting the lower temperature and lower humidity of the environment during the pre-gel treatment, and the treatment time, so that the volatilization of the solvent in the casting liquid and the absorption of water in the environment in the pre-gel stage are less, therefore, the overall change of the casting liquid system is small, the pre-gel nucleation process is relatively slow, and the higher good solvent content of the phase separation bath in the phase separation solidification stage makes the casting liquid tend to slowly separate into phases to form a macroporous structure in the phase separation solidification stage, while the phase separation speed of the part that has been nucleated in the pre-gel stage is slightly faster, forming a partial microporous structure. See the table below for details.

[0084] Example 6

[0085] The main difference between Example 6 and Example 1 is that the roller spacing is controlled in step S2 to obtain a lower thickness of the separator. In addition, during phase separation solidification, the temperature difference between the phase separation bath and the casting liquid is 15°C, and the lower phase separation bath temperature reduces the stability of the casting liquid. See the table below for details.

[0086] Example 7

[0087] The main difference between Example 7 and Example 1 is that the roller spacing is controlled in step S2 to obtain a thicker separator, and in addition, during phase separation solidification, the temperature difference between the phase separation bath and the casting solution is 10° C. See the table below for details.

[0088] Comparative Example

[0089] Comparative Example 1

[0090] The main difference between Comparative Example 1 and Example 1 is that the amount of high molecular weight polymer added is greatly increased and the amount of inorganic hydrophilic particles added is reduced, so that only a small amount of zirconium dioxide particles are contained in the finally prepared diaphragm.

[0091] Comparative Example 2

[0092] The main difference between Comparative Example 2 and Example 2 is that, on the basis of unchanged total solid content, the amount of high molecular weight polymer is greatly reduced and the amount of inorganic hydrophilic particles is greatly increased, and all inorganic hydrophilic particles are fine particles with an average particle size of 30 nm, so that the final diaphragm contains a large number of small-size zirconium dioxide particles.

[0093] Comparative Example 3

[0094] The main difference between Comparative Example 3 and Comparative Example 2 is that the inorganic hydrophilic particles do not use fine particles with an average particle size of 30nm, but use coarse particles with an average particle size of 1.5μm (i.e., 1500nm), so that the final diaphragm contains a large number of large-size zirconium dioxide particles.

[0095] Table 1 Process parameters of various embodiments and comparative examples

[0096]

[0097]

[0098] Performance tests and parameters

[0099] The performance of the diaphragms prepared in the embodiments and comparative examples was tested using the aforementioned test methods and recorded in the following table:

[0100] Table 2 Performance parameters of various embodiments and comparative examples

[0101]

[0102]

[0103] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0104] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An alkaline water electrolysis membrane, comprising a porous carrier and a porous hydrophilic layer disposed on both sides of the porous carrier, wherein the porous hydrophilic layer comprises a high molecular polymer and inorganic hydrophilic particles, and the porous hydrophilic layer at least partially penetrates into the pore structure of the porous carrier, characterized in that: The alkaline water electrolysis membrane satisfies the following conditions simultaneously: (1) The water contact angles on both sides of the alkaline water electrolysis membrane are greater than or equal to 60°; (2) The pore accessibility of the alkaline water electrolysis membrane is 90%-99%, wherein the pore accessibility is the ratio of the alkali absorption rate of the alkaline water electrolysis membrane when immersed in a 30wt% KOH solution at 60°C for 4 hours to the alkali absorption rate of the alkaline water electrolysis membrane when immersed in a 30wt% KOH solution at 90°C for 4 hours.

2. The alkaline water electrolysis membrane according to claim 1, characterized in that: The pore accessibility of the alkaline water electrolysis membrane is 92%-98%, and the water contact angles on both sides of the alkaline water electrolysis membrane are less than or equal to 80°.

3. The alkaline water electrolysis membrane according to claim 1 or 2, characterized in that: The alkali absorption rate Q of the alkaline water electrolysis membrane is 70%-90%, and the alkali absorption rate Q is calculated by the following formula: Q=(M1-M0) / M0, wherein M1 is the mass of the alkaline water electrolysis membrane per unit area in a saturated wet state after being immersed in a 30wt% KOH solution for 4 hours at 90°C, and its unit is g; M0 is the mass of the alkaline water electrolysis membrane per unit area in a dry state, and its unit is g.

4. The alkaline water electrolysis membrane according to claim 1 or 2, characterized in that: The SEM average pore size of the surface pores of the alkaline water electrolysis membrane is 200nm-1200nm, and / or the pore area percentage of the surface pores of the alkaline water electrolysis membrane on the surface of the alkaline water electrolysis membrane is 20%-60%.

5. The alkaline water electrolysis membrane according to claim 4, characterized in that: The ratio of the SEM median pore size to the SEM average pore size of the surface pores of the alkaline water electrolysis membrane is 0.7-1.

2.

6. The alkaline water electrolysis membrane according to claim 4, characterized in that: On the surface of the alkaline water electrolysis membrane, the average value of the minimum distance between adjacent pore structures is 100nm-500nm.

7. The alkaline water electrolysis membrane according to claim 1 or 2, characterized in that: The IPA initial bubble point of the alkaline water electrolysis membrane is not less than 0.8 bar, and the PMI minimum pore size of the alkaline water electrolysis membrane is not less than 10 nm.

8. The alkaline water electrolysis membrane according to claim 1 or 2, characterized in that: The PMI average pore size of the alkaline water electrolysis membrane is 15nm-50nm, and the porosity of the alkaline water electrolysis membrane is 50%-70%.

9. The alkaline water electrolysis membrane according to claim 1 or 2, characterized in that: The thickness of the alkaline water electrolysis membrane is 150 μm-600 μm, and the ratio of the SEM average particle size of the inorganic hydrophilic particles to the thickness of the alkaline water electrolysis membrane is 5 nm / 100 μm-150 nm / 100 μm.

10. The alkaline water electrolysis membrane according to claim 1, characterized in that: The alkaline water electrolysis membrane also satisfies at least one of the following conditions: (1) Under a pressure difference of 5 bar, the air permeability of the alkaline water electrolysis membrane is 2 L / min / cm 2 -6.5L / min / cm 2 ; (2) After being placed in water at 100° C. for 15 min, the dimensional change rate of the alkaline water electrolysis membrane is no more than 3%; (3) In a 90° C., 30 wt % KOH solution, the ionic resistance per unit thickness of the alkaline water electrolysis membrane is not greater than 35 mΩ·cm2 / 100 μm.

11. A process for preparing an alkaline water electrolysis membrane according to any one of claims 1 to 10, characterized in that: The process steps include: S1. Preparation of casting solution. First, the inorganic hydrophilic particles are mixed with the solvent system and stirred to disperse. Then, a polymer is added to fully dissolve to obtain a casting solution. In the casting solution, the total mass of the polymer and the inorganic hydrophilic particles accounts for 15wt%-25wt%, and the mass ratio of the polymer and the inorganic hydrophilic particles is 1:2-1:

8. The inorganic hydrophilic particles include fine particles with an average particle size of 30nm-350nm and coarse particles with an average particle size of 70nm-500nm. The average particle size of the fine particles is smaller than that of the coarse particles. The ratio of the fine particles to the coarse particles is 5:1-10:

1. The solvent system includes a first good solvent and a first poor solvent, and the mass ratio of the first good solvent is 80wt%-90wt%. S2, casting, casting the casting liquid onto the porous carrier to form a coating film; S3, pre-gelling, placing the coated film in an environment with a humidity of 70% RH-90% RH and a temperature of 50°C-70°C for pre-treatment for 5s-20s to obtain a gel film; S4, phase separation solidification, placing the gel film in a phase separation bath to completely phase separate and solidify the casting liquid to obtain a solidified film, wherein the phase separation bath comprises a second good solvent and a second poor solvent, and the mass proportion of the second good solvent is 5%-15%, and the temperature of the phase separation bath is 10°C-15°C lower than the temperature of the casting liquid; S5, post-treatment, washing and drying the solidified film to obtain an alkaline water electrolysis membrane.

12. The process for preparing the alkaline water electrolysis membrane according to claim 11, characterized in that: A water-soluble inorganic salt is also added to the casting solution, the amount of the water-soluble inorganic salt added is 0.05-0.1 times the mass of the inorganic hydrophilic particles added, and the water-soluble inorganic salt is at least one of calcium chloride, magnesium chloride and sodium chloride; and when preparing the casting solution, the water-soluble inorganic salt and the inorganic hydrophilic particles are added together into the solvent system for blending and dispersion.

13. The process for preparing an alkaline water electrolysis membrane according to claim 11, characterized in that: The first good solvent and the second good solvent are each independently selected from at least one of butyl lactate, dimethyl sulfoxide, dimethylformamide, caprolactam, methyl acetate, ethyl acetate, N-ethylpyrrolidone, dimethylacetamide and N-methylpyrrolidone, and the first poor solvent and the second poor solvent are both water.

14. An alkaline water electrolysis device, characterized in that: The alkaline water electrolysis device comprises the alkaline water electrolysis membrane as described in any one of claims 1-10.

Citation Information

Patent Citations

  • Preparation method of organic-inorganic composite membrane in alkaline electrolysis device

    CN115125582A

  • High-hydrophilicity alkaline electrolyzed water diaphragm and preparation method thereof

    CN116334690A